Husein Bračković: A Short History of Events in Herzegovina - Fajić, Zejnil (Prilozi za orijentalnu filologiju, 2017)
Husein Bračković came originally from Trebinje. He lived and worked in the second half of the XIXth, and the beginning of the XXth century. He was a state-official and worked in various offices from 1857 to 1878. After the occupation of Bosnia and Herzegovina by the Austrians, he lived in Mostar, where he died. The date of his death is unknown. He wrote the above-mentioned work there in 1895. The manuscript of this work is in Turkisch, and is preserved in the Ghazi Husref-Bey Library in Sarajevo, No. R-1156. The work consists of an introduction, three chapters and an appendix. In his introduction the author explains his reasons for writing this work, then he goes on to give some information about himself, and finally informs the reader about the sources he has used. The first chapter deals with the administration of Ali-Pasha Rizvanbegović - Stočević in Herzegovina (1833 - 1851), as well as the administration before his coming to power. Ali-Pasha himself, as a personality and statesman, is described, and also his assassination by Omer-pasha Latas in the vicinity of Banja Luka. The second chapter, the longest, deals with the situation in Herzegovina, which was almost constantly in a state of war. Numerous battles are described with their causes, the names of the Turkish generals in different battles, and the names of the leaders of insurgents are given. According to the author, the Turkish authorities tried to settle their disputes with the rebels peacefully, even making them some concessions, but all attempts came to nothing. The appointment of Omer-Pasha Latas was one of these attempts. ln the same chapter the entry of the Sultan's Army into Mostar at the time of Omer-Pasha Latas, is described by the author as the conquest of Herzegovina. The third chapter deals with the occupation of Herzegovina by the Austrian Army, with special emphasis on the resistance of the local population in some places in Herzegovina, as well as with the killing of some well-known personalities, who opposed the popular resistance to the Austrian occupation. The administration in Herzegovina is discussed briefly in the appendix. The author records and mentions, according to rank, all government posts, monthly salaries of the holders, and various government and administrative committees that met at fixed time to deal with the problems of state. The police, the manner of collecting the tithe and other taxes, judges (kadiB) of the liva. teachers and scholars are described, with special comment on the best-known learnied men in certain towns of Herzegovina; the administration, construction activites in the sanjak, waqfs, and inheritance in the sanjak, customs-duties in Herzegovina, relations of landowners and lessees of cifli.